Writing Twentieth-Century Music History in Postmodern Times - Tillman, Joakim (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2000)
STM-Online Special: Musikhistoria och den högre musikutbildningen i förändringens tid Music History and Higher Music Education in a Time of Change Joakim Tillman Writing Twentieth-Century Music History in Postmodern Times Departing from Christopher Williams’s criticism of Robert P. Morgan’s handbook on twentieth-century music, this article discusses important problems concerning the writing of twentieth-century music history, including the selection of composers and canon formation, historical importance and construction of history, and relevance and scope of context. The infinite variety of reality makes it impossible to describe everything from all conceivable points of view. Therefore, history must be written from some perspective, horizon, or whatever you chose to call it. The article argues that in a time where all metanarratives have been abandoned, modernism can no longer be the only relevant perspective in the writing of twentieth-century art music, at least not in a general handbook intended for courses that form students’ opinions of the subject. Instead we should make students aware of different problems and perspectives involved in the writing of twentieth-century music history. Thus, the best solution in a pluralistic climate is an eclectic approach, which does not fall into the trap of total relativism.